Tingkat Pengetahuan Mengenai Kepatuhan Minum Obat Pada Pasien Hipertensi Rawat Jalan Di Puskesmas “X” Banyuwangi Tahun 2022 - Isma Oktadiana; Siti Fatimah Sultan; Rena Meutia; Cut Intan Annisa Puteri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Hypertension is an increase in blood pressure in the arteries that exceeds normal limits with an increase in systolic blood pressure> 140 mmHg and diastolic blood pressure> 90 mmHg. The level of knowledge about hypertension is one of the factors that can affect adherence to lifestyle and treatment of hypertension. This study aims to determine the level of knowledge and medication adherence in hypertensive patients and to determine the relationship between the level of knowledge on medication adherence in hypertensive patients at the